IDENTIFICATION OFPEAT SOIL PHYSICAL CHANGES IN THREE TYPES OF LAND USE IN WEST KALIMANTAN PROVINCE KUBU RAYA - ., Mateus aba; Suryadi, MP, Dr.Ir. Urai Edi (Jurnal Sains Pertanian Equator, 2016)
The most obvious peat land conversion nowadays is the conversion of peatlands for plantations and the palm oil industry. As a result of the land clearing activities in large-scale in peat soil, it caused peat land damage. Peatland degradation in Rasau Jaya district today can be seen from the changes in physical properties of peat soil. A real change of physical properties of peat soil today is the peat layer depletion due to drainage, and low power of loadbearing structure of the soil, so many palm trees grow sideways. The research objective was to identify changes in physical properties of peat soil of secondary forests, open land, and oil palm plantations.Soil samples were collected from study sites in kubu raya district of west Kalimantan. Parameters include water table in each site and in secondary tunnels, field capacity water content, bulk density, particle weight, porosity, hydraulic conductivity, and soil maturity levels. The results showed that water table was deeper in temporarily open land (66,35 cm) and in oil plam plantation (64, 0 cm), and shallow in secondary forest (54,26 cm). Water table at secondary tunnels was also deeper in temporarily open land (109 cm), higher in oil plam plantation (100, 5 cm), and highest in secondary forest (99,25 cm). Field capacity content was highest in secondary forest (79,65%), lower in temporarily open land (77,62 %), and lowest in oil palm plantationnn (75,41 %). Furthermore, bulk density was highest in oil palm plantation (0,46 g/cm3),lowest in temporarily open land (0,27 g/cm3), and lower ini seconday forest (0,22 g/cm3). Particle weight was also highest in oil palm plantation (1,59 g/cm3), lower ini temporarily open land (1,34 g/cm3), and lowest in secondary forest (1,26 g/cm3). Meanwhile, porosity was lowest in oil palm plantation (70,92 %), higher in temporarily open land (78,94 %), and highest in secondary forest (81,80 %). Hydraulic conductivity was also highest in oil palm plantation (10,61 cm/hour), lower in temporarily open land (7,88 cm/ hour), and lowes in secondary forest (5,23 cm/hour). Finally, there were vary in soil maturity levels, namely hemik and fibric in seconday forest, hemic, fibric, and sapric in temporarily open land, and only sapric in oil palm plantation. Conclusion, different management types had caused changes in soil physical properties of peatland.